Neural correlates of visual perceptual expertise: Evidence from cognitive neuroscience using functional neuroimaging - Gegenfurtner, Andreas; Kok, Ellen M.; van Geel, Koos; de Bruin, Anique B. H.; Sorger, Bettina (Frontline Learning Research, 2017)
Functional neuroimaging is a useful approach to study the neural correlates of visual perceptual expertise. The purpose of this paper is to review the functional-neuroimaging methods that have been implemented in previous research in this context. First, we will discuss research questions typically addressed in visual expertise research. Second, we will describe which kinds of stimuli are employed and which functional-neuroimaging techniques are implemented in this kind of research, with a special focus on electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). Third, we will summarize the outcomes of recent studies that addressed the neural correlates of visual expertise and will particularly focus on studies that examined the neural correlates of visual expertise in medical image diagnosis. Finally, the review closes with a discussion of the benefits, caveats, and future directions of cognitive-neuroscience research for studying visual expertise.